Analisis Bibliometrik Bimbingan Karier dengan Media Batik Jumputan untuk Meningkatkan Culture Awareness pada Anak - Putri Agung Amanda Maharani; Ari Khusumadewi; Budi Purwoko; Evi Winingsih (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article aims to bibliometrically analyze the use of jumputan batik media in career guidance to increase cultural awareness in children. Using a bibliometric analysis approach, this study identifies trends, publication patterns, and relationships between the topics of career guidance, culture, and learning media, specifically jumputan batik, which serves as a tool to foster cultural awareness. The analysis showed that the integration of jumputan batik media in career guidance delivery is effective in introducing children to local cultural values, thus enhancing their understanding of cultural diversity. The research can also reveal that the approach used can enrich children’s learning experience in developing career skills and can also strengthen their cultural identity. Overall, this study suggests that career guidance using local cultural media, such as jumputan batik, has great potential to support in the formation of children’s character who are adaptive and sensitive to cultural differences in the context of an increasingly global and multicultural world of work.